2012
DOI: 10.1111/j.1398-9995.2012.02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of asthma – a new approach

Abstract: Current definition of asthma involves four cornerstones: inflammation, hyperresponsiveness, bronchoconstriction, and symptoms. In research, the symptoms have had the slightest attention. According to international guidelines, the asthma symptoms are episodic breathlessness, wheeze, cough, tightness of the chest, and shortness of breath. As there are several symptoms, a primary question is how they are related to bronchoconstriction, the main clinical feature of asthma. Symptoms and lung function tests are regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 76 publications
0
14
0
2
Order By: Relevance
“…One limitation is that we did not have information on asthma severity, including duration of asthma episodes, even though it could be hypothesized that the magnitude of disease risk may be lower in offspring of mothers with less severe asthma during pregnancy. 4,68 Moreover, we were not able to operationalize asthma according to a specific definition (eg, taking into account key characteristics, such as inflammation, hyperresponsiveness, reversible airway obstruction, and respiratory symptoms 17,18 ), as the required information, including diagnostic test results or information on asthma subtypes, was not available from the interviews, and it is hardly feasible in a large cohort to assess such details. However, validation of self-reported asthma against physician diagnoses, 19 together with the high percentage of women with asthma during pregnancy and a doctor-diagnosis of lifetime asthma in this study, allows to at least approach the definition of asthma according to the ICD-10.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…One limitation is that we did not have information on asthma severity, including duration of asthma episodes, even though it could be hypothesized that the magnitude of disease risk may be lower in offspring of mothers with less severe asthma during pregnancy. 4,68 Moreover, we were not able to operationalize asthma according to a specific definition (eg, taking into account key characteristics, such as inflammation, hyperresponsiveness, reversible airway obstruction, and respiratory symptoms 17,18 ), as the required information, including diagnostic test results or information on asthma subtypes, was not available from the interviews, and it is hardly feasible in a large cohort to assess such details. However, validation of self-reported asthma against physician diagnoses, 19 together with the high percentage of women with asthma during pregnancy and a doctor-diagnosis of lifetime asthma in this study, allows to at least approach the definition of asthma according to the ICD-10.…”
Section: Figurementioning
confidence: 99%
“…A mother was considered to have asthma during pregnancy if self-reported asthma of any type had occurred at any time during the current pregnancy, without further specification according to previously suggested asthma definitions. 17,18 Women were asked if they had a lifetime history of asthma, if a doctor had diagnosed the asthma, and if they were suffering/had suffered from asthma during pregnancy. The agreement of case ascertainment by patient self-report and physician diagnosis has been shown to be high (k: 0.83), 19 and additional analysis of the study cohort revealed that 95.85% of women reporting lifetime asthma had received this diagnosis by a doctor.…”
Section: Study Cohortmentioning
confidence: 99%
“…All too often, asthma is used as a synonym of dyspnoea [51]. Indeed, so heterogeneous are the phenotypes of what can be referred to as asthma that there have been calls to abandon the use of the term altogether [52].…”
Section: Definitions and Pathologymentioning
confidence: 99%
“…27-29, 31, 32, 34-55 Follow-up studies have shown that physician-diagnosed asthma cannot be verified in up to one third of patients investigated. [56][57][58][59][60] As many of these non-asthma patients still have symptoms other non-obstructive mechanisms must exist. 60 The high proportion of treatment failure and misdiagnosis may justify the testing of new theories.…”
Section: Introductionmentioning
confidence: 99%